Pengaruh Kematangan Emosi, Religiusitas, Kepercayaan Diri, Sosial Ekonomi Keluarga, Dan Lingkungan Sekolah Tehadap Motivasi Belajar Siswa IPS di SMA Negeri 13 Padang - Sarita Ramli (STKIP PGRI Sumatera Barat, 2021)
This study aims to analyze the influence of classroom management, students' learning interests, mobile phone usage, confidence and parenting patterns stimultan to the learning achievements of grade VII students of SMP Negeri 3 Palembayan. The results showed that: (1) there was a significant influence between partial classroom management on student learning achievement with a coefficient score of 0.137, a thitung score of 3,197>ttabel of 1,998; (2) there is a significant influence between students' partial learning interest in student learning achievement with a coefficient of 0.181, a value of 4,728>ttabel of 1,998; (3) there is a significant influence on the partial use of mobile phones on student learning achievement with a coefficient of 0.175, a value of 6,089>ttabel of 1,998; (4) there is a significant influence of partial confidence on student learning achievement with a coefficient of 0.073 and a thitung score of 2,453>ttabel of 1,998; (5) there is a significant influence of partial parental parenting patterns on student learning achievement with a coefficient score of 0.089 and a thitung score of 2,204>ttabel of 1,998; (6) there is a significant influence between classroom management, student learning interests, mobile phone use, self-confidence and parenting patterns stimultan to student learning achievement with a Tcalculate of 44,331>Ftabel2.52.